Review on potential therapeutic effect of Morinda citrifolia L. - Ahmad, Aziatul Natasha; Mat Daud, Zulfitri 'Azuan; Ismail, Amin (Elsevier, 2016)
Morinda citrifolia L. is traditionally being used as medicinal herb in Polynesia. Previous studies have reported that this plant can be used as a medicinal plant to prevent and cure several diseases. In this paper, recent research regarding the potential therapeutic effect of M. citrifolia is reviewed. This plant includes broad range of therapeutic effect such as anti-diabetic effects, antibacterial activity, anti-cancer and antioxidant activity. The presence of antioxidant properties and phenolic compound in M. citrifolia were demonstrated as anti-diabetic effects and antibacterial agents, respectively. Besides, M. citrifolia act as anti-cancer properties because it enhanced the host of immune system. The primary aim of this paper is to review available information on potential therapeutic effects and nutritional advances related to M. citrifolia.